Sequence dependent modulating effect of camptothecin on the DNA-cleaving activity of the calf thymus type I topoisomerase. - Gromova, I I (1990)
High-resolution mapping of topol cleavages in the regions of human DNA including the oncogene c-Ha-ras and p53, has revealed three kinds of topol cleavage sites: cleavage sites not affected by camptothecin; cleavage sites reinforced only in the presence of camptothecin, and cleavage sites which weaken in the presence of camptothecin. Statistical analysis of sequences revealed certain nucleotide or dinucleotide preferences for three groups studied. The preferences in camptothecin-reduced sites predominate upstream from the cleavage point, whereas in camptothecin-induced sites the situation is reversed. The influence of camptothecin on cleavage sites induced by two molecular forms of topol has been also studied.